Anaphylaxis and digital medicine. Issue 5 (October 2021) - Anto, Aram; Sousa-Pinto, Bernardo; Bousquet, Jean
Abstract : Purpose of review: Digital medicine (mHealth) aims to help patients and healthcare providers (HCPs) improve and facilitate the provision of patient care. It encompasses equipment/connected medical devices, mHealth services and mHealth apps (apps). An updated review on digital health in anaphylaxis is proposed. Recent findings: In anaphylaxis, mHealth is used in electronic health records and registries. It will greatly benefit from the new International Classification of Diseases-11 rules and artificial intelligence. Telehealth has been revolutionised by the coronavirus disease 2019 pandemic, and lessons learnt should be extended to shared decision making in anaphylaxis. Very few nonvalidated apps exist and there is an urgent need to develop and validate such tools. Summary: Although digital health appears to be of great importance in anaphylaxis, it is still insufficiently used.